2009
DOI: 10.1093/gerona/glp074
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Activity and Isoenzyme Expression in the Senescence-Accelerated Mouse P8 Model of Alzheimer's Disease: Effects of Anti-Amyloid Antibody and Antisense Treatments

Abstract: Amyloid beta protein (Abeta) in Alzheimer's disease induces oxidative stress through several mechanisms, including stimulation of nitric oxide synthase (NOS) activity. We examined NOS activity and expression in the senescence-accelerated mouse P8 (SAMP8) line. The SAMP8 strain develops with aging cognitive impairments, increases in Abeta, and oxidative stress, all reversed by amyloid precursor protein antisense or Abeta antibody treatment. We found here that hippocampal NOS activity in 12-month-old SAMP8 mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…There is also evidence linking ADMA and NO regulation with cognitive dysfunction [57]. Increases in ADMA lead to a decline in NO, which causes reduction in brain blood flow, white matter fiber edema and demyelination, and generation of β-amyloid precursor protein, ultimately leading to learning and memory disorders [58]. Thus, S100B and ADMA may be potential therapeutic targets, and inhibition or blockade of their pathologic effects in patients with elevated levels may help to minimize cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence linking ADMA and NO regulation with cognitive dysfunction [57]. Increases in ADMA lead to a decline in NO, which causes reduction in brain blood flow, white matter fiber edema and demyelination, and generation of β-amyloid precursor protein, ultimately leading to learning and memory disorders [58]. Thus, S100B and ADMA may be potential therapeutic targets, and inhibition or blockade of their pathologic effects in patients with elevated levels may help to minimize cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…As a free radical, NO reacts with superoxide radicals to form peroxynitrite and results in neurotoxicity and cell apoptosis under an abnormal physiological status, which is involved in the pathogenesis of AD and Parkinson's disease (27). Previous study has shown that administration of LSPC for 3 months resulted in NO inhibition in the Values are expressed as a mean±SD (n=10).…”
Section: Effects Of Lspc On Step-down Avoidance Testingmentioning
confidence: 99%
“…Interestingly, genes and proteins that undergo significant alterations in SAMP8 brains are related to the following functional categories: neuroprotection, signal transduction, immune response, energy metabolism, mitochondrion, protein folding and degradation, reactive oxygen species production, cytoskeleton and transport, lipid abnormalities and cholinergic dysfunction (Butterfield and Poon, 2005; for review, see Sowell and Butterfield, 2010). The SAMP8 strain has proven to be a relevant model for AD and several treatment strategies have been studied in these mice, including antioxidants (Farr et al ., 2003; Poon et al ., 2005; Nishimura et al ., 2006; Shih et al ., 2010), antisense oligonucleotides, directed at the Aβ region of the amyloid precursor protein (APP) gene (Kumar et al ., 2000; Banks et al ., 2001; Poon et al ., 2004; Ali et al ., 2009), consistent with the notion that SAMP8 cognitive changes are associated with Aβ‐associated oxidative stress. Besides pharmacological interventions, dietary restriction as a way to increase lifespan and improve health, and its effect on various functional categories that are affected in SAMP8 with ageing, as described above, was recently evaluated (Tajes et al ., 2010).…”
Section: Spontaneous Modelsmentioning
confidence: 99%